2022
DOI: 10.1038/s41598-022-25738-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CCAT2, involving miR-34a/TGF-β1/Smad4 signaling, regulate hepatic stellate cells proliferation

Abstract: AbstractmiR-34a targeting on Smad4 plays important role in TGF-β1 pathway which is a dominant factor for balancing collagen production and degradation in hepatic stellate cells. TGF-β1/Smad4 regulated collagen deposition is a hallmark of hepatic fibrosis. The potential regulation on miR-34a by LncRNAs in hepatic stellate cells (HSCs) is still reserved to be revealed. In current study, it was hypothesized that a miR-34a interactor, lncRNA CCAT2 may regulate TGF-β1 pathway in liver fibrotic remodeling. The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…35) Beyond this tumor-promoting role, CCAT2 can also regulate hepatic stellate cell proliferation and apoptosis. 36) Huang et al found that the detection of CCAT2 levels in patient serum could be used to predict the rupture of atherosclerotic plaques. 20) It also suggests that CCAT2 is associated with cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…35) Beyond this tumor-promoting role, CCAT2 can also regulate hepatic stellate cell proliferation and apoptosis. 36) Huang et al found that the detection of CCAT2 levels in patient serum could be used to predict the rupture of atherosclerotic plaques. 20) It also suggests that CCAT2 is associated with cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal miR-210 uptake from ECs promotes angiogenesis by targeting specific processes depending on the tumor microenvironment [ 100 ]. The chromatin epigenetic regulation of proangiogenic genes has also been attributed to different lncRNA packaged in EVs, although the mechanism is not fully elucidated [ 101 , 102 , 103 ] ( Figure 2 ). LncRNAs can work as molecular scaffold, assembling several chromatin regulator proteins and reshaping the DNA structure in the nucleus and thus favoring the transcription or silencing of target genes [ 104 ].…”
Section: Basic Mechanisms and Epigenetic Role Of Evs In Tumor Vascula...mentioning
confidence: 99%